FORMULASI EKSTRAK KLOROFORM DAUN BELIMBING WULUH DALAM BENTUK SEDIAAN GEL dan UJI AKTIVITAS ANTIBAKTERI TERHADAP Staphylococcus epidermidis - Tan, Verawaty; Rahmadhani, Nova Tri; Dewi, Irene Puspa (Jurnal Riset Kefarmasian Indonesia, 2019)
Herbal treatments are needed to treat various diseases, one of which is the leaves of Belimbing Wuluh (Averrhoa bilimbi L.). The aim of this study was to formulate chloroform extract of Belimbing Wuluh’s leaf (Averrhoa bilimbi L.) into gel preparations that were good, effective, and safe to use and to determine the antibacterial activity of chloroform extract of Belimbing Wuluh (Averrhoa bilimbi L.) leaf extract to Staphylococcus epidermidis by well method. The results showed that form of gel is a thick, dark green, the distinctive smell of Wuluh starfruit leaf extract, homogeneous, good skin pH, good washing and does not irritate the skin. This study uses Nutrient Agar media as a culture medium for Staphylococcus epidermidis bacteria. The results indicate that the chloroform extract gel leaves of belimbing wuluh leaves in formula 1 (10%), formula 2 (20%), and formula 3 (30%) were able to inhibit the growth of Staphylococcus epidermidis bacteria. In formula 3 (30%) gel extract of belimbing wuluh leaves has the widest zone of inhibition compared to other dosage formulas. The statistical test using the One Way ANOVA test showed a significant difference from the average diameter of the inhibition zone between all concentrations of chloroform extract gel leaves of belimbing wuluh leaves that were significant with (α ˂ 0.05).